2019
DOI: 10.1111/gcb.14712
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for behavioral rescue under rapid environmental change

Abstract: Laboratory measurements of physiological and demographic tolerances are important in understanding the impact of climate change on species diversity; however, it has been recognized that forecasts based solely on these laboratory estimates overestimate risk by omitting the capacity for species to utilize microclimatic variation via behavioral adjustments in activity patterns or habitat choice. The complex, and often context‐dependent nature, of microclimate utilization has been an impediment to the advancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 47 publications
(119 reference statements)
2
49
1
Order By: Relevance
“…Indeed, our behavioral preference test showed that females avoided near-lethal temperatures even if by doing so they had to deal with lower oxygen levels at lower temperatures. This behavioral preference of T. californicus , which remains to be demonstrated in a natural setting, supports a recent prediction that behavioral responses of natural populations may enable them to exploit microclimatic variations in heterogeneous habitats as an important mechanism to rescue species from rapidly changing environments 17 , 18 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Indeed, our behavioral preference test showed that females avoided near-lethal temperatures even if by doing so they had to deal with lower oxygen levels at lower temperatures. This behavioral preference of T. californicus , which remains to be demonstrated in a natural setting, supports a recent prediction that behavioral responses of natural populations may enable them to exploit microclimatic variations in heterogeneous habitats as an important mechanism to rescue species from rapidly changing environments 17 , 18 .…”
Section: Discussionsupporting
confidence: 82%
“…For example, extreme temperatures decrease the oxygen solubility while simultaneously increasing the organism’s oxygen demand, hence intensifying hypoxic stress on marine species 7 , 13 . To locally survive, organisms may have to adjust their physiology 14 – 16 and/or behaviors 14 , 17 , 18 to cope with or avoid stressful conditions. However, we know relatively little about the prevalence and magnitude of the present-day interactions among stressors and their impacts on marine species 10 12 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations